Streptomyces spp. from rhizosphere soil of maize with potential as plant growth promoter - Aris Tri Wahyudi; J.A. Priyanto; HANIFA NUR Fijrina; HIMA DEWI Mariastuti; ABDJAD ASIH Nawangsih (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wahyudi AT, Priyanto JA, Fijrina HN, Mariastuti HD, Nawangsih AA. 2019. Streptomyces spp. from rhizosphere soil of maize with potential as plant growth promoter. Biodiversitas 20: 2547-2553. Actinomycete is one group of rhizobacteria that plays an important role as a plant growth promoter. This study was aimed to evaluate the potential of Actinomycetes isolated from maize rhizosphere in promoting plant growth in vitro including their ability to produce IAA, promote maize sprout growth, solubilize phosphate, and grow in N-free medium. Thirty isolates have been isolated from maize rhizosphere using a spread plate method. All 30 isolates were probably not pathogenic to plants as tested by hypersensitivity reaction test on tobacco leaves. Based on the colorimetric assay, 30 isolates (100%) were able to produce IAA with concentrations ranging from 1.05 to 26.89 ppm. The highest concentration of IAA (26.89 ppm) produced by ARJ 21 and the lowest IAA concentration (1.05 ppm) produced by ARJ 12. By using the Ragdoll method, it showed that 9 isolates (30%) were able to promote maize sprout growth significantly on five growth parameters including primary root length, stem length, number of lateral roots, wet weight and dry weight. Twenty-one isolates (70%) were capable of solubilizing phosphate in Pikovskaya medium containing tricalcium phosphate. Also, 30 isolates (100%) were able to grow on N-free medium, suggesting their ability to fix nitrogen. Based on 16S-rRNA, five potential isolates with plant growth-promoting properties were highly similar to Streptomyces spp. Based on their potential characters, these Actinomycetes isolates have the potential to be further developed as a biofertilizer agent for sustainable maize farming.